N-Heterocyclic Carbene Switchable Radical- or Benzyne-Meditated Arylation of Thiols Using DMF/KOt-Bu - Puschnig, Johannes; Greatrex, Ben W. (Synlett, 2024)
A mild, metal, and photoredox-free direct arylation of alkyl and aryl thiols with aryl iodides using a DMF/KOt-Bu system has been developed. In the absence of an N-heterocyclic carbene (NHC) additive, the reaction proceeds via a benzyne intermediate and was suitable for the substitution of thiols with phenyl, while the presence of an NHC or phenanthroline derivative improves regioselectivity for the reaction of substituted aryl iodides via a radical pathway. This protocol features inexpensive materials and good substrate scope and could be useful in the arylation of aryl and alkyl thiols.
Keywords: metal-free coupling; thiols; aryl halides; N-heterocyclic carbene; benzyne